Scarlet nights : an Edilean novel - Deveraux, Jude.; Deveraux, Jude. (New York : Pocket Star Books, 2011)
In Edilean, Virginia, undercover detective Mike Newland uses Sara Shaw to track down a woman who is one of the most notorious criminals in the United States--and also happens to be the mother of Greg Anders, the man who Sara plans to marry and who leaves her without explanation three weeks before the wedding.
Cover title: Scarlet nights : a novel.
Keywords: Secrets -- Fiction; Undercover operations -- Fiction; Missing persons -- Fiction; Female offenders -- Fiction; Fiances -- Fiction; Impostors and imposture -- Fiction; Virginia -- Fiction; Detective and mystery stories; Mystery fiction; Love stories